What Drives Clean Cooking Solutions in Africa? An Empirical Study in Kenya and Nigeria - Matsubara, Fumihiko (International Journal of Energy Economics and Policy, 2024)
Improved cookstoves and clean cooking solutions have been garnering increasing attention in Africa owing to their carbon credits. The energy ladder theory indicates that the utilisation rate of clean cooking solutions increases when the Gross Domestic Product (GDP) per capita increases. This study analyses other factors that may influence the utilisation rate of clean cooking solutions, such as population, women household heads, electricity utilisation, and improved water. The results show that GDP per capita correlated more highly with clean cooking solutions than with other factors. This study also determined that higher electricity access rates did not lead to high utilisation of electric cookstoves in Africa, likely due to the greater influence of traditional cooking methodologies and government policies. Through interviews, the study found that certain policies influence Kenya’s high adaptability and Nigeria’s low adaptability to clean cooking solutions.